The role of pulse oximetry in the diagnosis of cardiopulmonary complications of ERCP - Emin ALTIPARMAK; Orhan SEZGİN; Yıldıran SONGÜR; Yasemin KOŞAR; Ülkü SARITAŞ; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-